The moderating role of perceived vulnerability in the relationship between patriotism and consumer ethnocentrism - Wise Lozano, Jorge Alberto (My University, 2005)
This research establish that the consumer's perceived vulnerability to a threat is a relevant variable that modifies the preference for domestic origin products. This study demonstrates that perceived vulnerability to a threat such as damaging one's personal well-being is a relevant factor when consumers express their preference for domestic products, or consumer ethnocentrism. Using a model relating patriotism and consumer ethnocentrism, perception of vulnerability is shown to be a pure moderation variable affecting that relationship. The literature about ethnocentrism has failed to recognize relevant factors other than patriotism that influence the level of consumer ethnocentrism. One such relevant factor is the individual's perceived vulnerability to a threat. Using a Mexican sample of consumers, this study evidenced that patriotism is a relevant factor influencing the level of consumer ethnocentrism. Additionally the vi interaction between patriotism and perceived vulnerability is found to positively moderate that effect. Using scales previously developed of patriotism and consumer ethnocentrism the findings suggest that patriotic Mexicans will be ethnocentric consumers. However, they will increase their ethnocentric feelings due to a perception of vulnerability to a threat affecting their well-being and standard of living.
Keywords: Moderating role; Consumer ethnocentrism; Percieved vulnerability patriotism; Campus Mexicali